2011
DOI: 10.1523/jneurosci.1425-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prior Expectation Mediates Neural Adaptation to Repeated Sounds in the Auditory Cortex: An MEG Study

Abstract: Repetition suppression, the phenomenon that the second presentation of a stimulus attenuates neural activity, is typically viewed as an automatic consequence of repeated stimulus presentation. However, a recent neuroimaging study has suggested that repetition suppression may be driven by top-down expectations. Here we examined whether and when repetition suppression can be modulated by top-down expectation. Participants listened to auditory stimuli in blocks where tone repetitions were either expected or unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
349
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(431 citation statements)
references
References 48 publications
(56 reference statements)
61
349
3
1
Order By: Relevance
“…As shown in Figure 7, the predictive currents anticipated the arrival of a second B sound and therefore produced a response to a nonexisting sound, as experimentally observed. Indeed, our results are tightly consistent with MEG and intracranial data obtained on a similar protocol (Hughes et al, 2001;Todorovic et al, 2011).…”
Section: Mmn To Omissionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 7, the predictive currents anticipated the arrival of a second B sound and therefore produced a response to a nonexisting sound, as experimentally observed. Indeed, our results are tightly consistent with MEG and intracranial data obtained on a similar protocol (Hughes et al, 2001;Todorovic et al, 2011).…”
Section: Mmn To Omissionsupporting
confidence: 91%
“…One of the most remarkable properties of the auditory system is that it can generate evoked responses to an absent but expected stimulus (Joutsiniemi and Hari, 1989;Raij et al, 1997;Yabe et al, 1997;Hughes et al, 2001;Todorovic et al, 2011;Wacongne et al, 2011). We similarly tested the response of our network to the omission of an expected sound.…”
Section: Mmn To Omissionmentioning
confidence: 99%
“…This decrease is consistent with the body of literature supporting predictive encoding (e.g., Friston, 2009;Mayrhauser et al, 2014;Rao & Ballard, 1999;Summerfield et al, 2008;Todorovic et al, 2011) and suggests that this system could benefit from reduced prediction error in the spatial domain. We conjecture that as the set of possible target locations becomes smaller the prediction error is resolved more quickly and efficiently, which produces less metabolic activation..…”
Section: Location Regularitiessupporting
confidence: 89%
“…Consistent with this view, Bubic et al (2011) found that different neural systems are involved in evaluating predictions regarding object identity, location, and presentation time. Other studies have shown that odd-ball (unexpected) auditory or visual events produce patterns corresponding to surprise or prediction error in respective sensory cortices (Kok et al, 2012;Mustovic et al, 2003;Todorovic, van Ede, Maris, & de Lange, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The former, linked to processes such as local neuronal stimulus specific adaptation (SSA; Ulanovsky et al2003; for a recent review, see Ayala & Malmierca, 2013), requires replication of a sound over time and leads to reduction in early components of the ERP (e.g., 40-60ms; Slabu et al2010). In contrast, expectation suppression is related to expectation of a pattern continuation (Summerfield et al 2008;Alink et al 2010;den Ouden et al 2010;Todorovic et al 2011), with an effect that is present in later ERP components (e.g, 100-200 ms).…”
Section: Discussionmentioning
confidence: 83%